Factors influencing students’ intention to study at University in the Faculty of Business Management at Universiti Teknologi MARA Cawangan Melaka Kampus Alor Gajah / Nur Afifah Mohd Nor Jafri - Mohd Nor Jafri, Nur Afifah (Faculty of Business and Management, 2018)
Numerous of university are increasing overtime, that make the university become intense in attracting potential students to study at university. As for the students, it becomes complicated to understand and choose the best programs and university. This is the key issue where the university needs to know the factors that influencing students’ intention to study at university.